Two new species of the genus Aalatettix Zheng & Mao (Orthoptera, Tetrigoidea, Tetrigidae) from Taiwan, China - Zheng, Fang-Qiang; Shi, Jian-Ping; Yin, Zhan (Zootaxa, 2015)
Two new species of the genus Aalatettix Zheng & Mao, 2002, namely Aalatettix yangi sp. nov. and Aalatettix xiai sp. nov. are described and illustrated. The new species Aalatettix yangi sp. nov. is allied to Aalatettix gibbosa Zheng, Cao & Chen, 2011, but upper margin of pronotum waved in lateral view, width of frontal ridge narrower than width of basal joint of antennae, hind tibiae dark brown, base not pale. The new species Aalatettix xiai sp. nov. is allied to Aalatettix yangi sp. nov., but length of pronotum shorter, not reaching epiproct, width of vertex 1.5 times diameter of eye, lateral carinae of pronotum contracted backward distinctly, posterior apex of lower margin angular on lateral lobe of pronotum, lower margin of median femur waved, antennae placed under lower margin of eyes. The type specimens are deposited in the National Museum of Natural Science, Taichung, Taiwan, China.